Cervical Medial Branch Block Volume Dependent Dispersion Patterns as a Predictor for Ablation Success: A Cadaveric Study. Issue 6 (15th March 2019) - Wahezi, Sayed E.; Molina, Jocelin J.; Alexeev, Edward; Georgy, John S.; Haramati, Nogah; Erosa, Stephen A.; Shah, Jay M.; Downie, Sherry
Abstract : Background: Neck pain is one of the most common causes of chronic pain and the fourth leading cause of disability worldwide; it is estimated that between 36% and 67% of this pain is due to facet arthropathy. For patients who have pain refractory to conservative treatments literature supports management with diagnostic cervical medial branch blocks (MBBs) to identify the associated facet innervation as the source of pain followed by therapeutic radiofrequency ablation (RFA) of the identified nerves. Cervical RFA has good published outcomes; however, the procedure is dependent upon the specificity of the diagnostic block to achieve maximal success. Currently, this prerequisite test has false positive rates between 27% and 63% and recent studies have shown that this may, in part, be a consequence of currently accepted injection volumes of 0.50 mL or more, which may decrease the sensitivity of MBBs. Objective: To evaluate the possible differences in volume dispersion between 0.25 and 0.50 mL of injectate during cervical MBBs. Study Design: Cadaveric study. Setting: An academic medical center in the United States. Patients: Not applicable. Methods: This was a cadaveric study in which six subjects were chosen with intact cervical spines. Cervical MBB were performed bilaterally at the midcervical spine, using a posterior approach under fluoroscopic guidance. 0.25 or 0.50 mL of a 9:1 solution of Omnipaque 180 mg iodine/mL and 1% medical grade methylene blue were administered on the left and right sides, respectively. Postinjection computed tomography (CT) imaging and gross dissection were performed to assess injectate spread. Main Outcome Measures: Outcome measures after using commonly injected volumes for cervical MBB, included visualized and measured spread (by CT and gross dissection) of cervical medial branch blocks, coating adjacent structures not targeted by RFA. Results: Postinjection CT imaging and cadaveric dissection demonstrated that, although both volumes adequately coated the medial branches, the 0.50 mL cohort reliably spread dorsally to superficial muscles (splenius) and nerves distant from the targeted nerves (dorsal motor branches to splenius), whereas the 0.25 mL injectate cohort was contained in the deep and intermediate muscular cervical layers directly juxtaposed to the targeted cMBBs. Conclusion: Results suggest that 0.50 mL injections of local anesthetic during cervical MBBs contacts many nonintended targets, thus decreasing the specificity of a targeted diagnostic cervical MBB. Furthermore, we demonstrated that 0.25 mL of injectate reliably bathed the cervical medial branches without extensive extravasation. This indicates that there would potentially be fewer local anesthetic effects on distant tissues, increasing the specificity of cervical MBBs and likely improving RFA planning.